ORAL HEALTH KNOWLEDGE AND ATTITUDE, ORAL HEALTH STATUS IN ELDERLY AND ITS IMPACT ON GENERAL WELL-BEING: PENGETAHUAN DAN PERILAKU TENTANG KESEHATAN RONGGA MULUT, STATUS KESEHATAN MULUT PADA LANSIA DAN IMPLIKASINYA PADA KESEHATAN UMUM - Abdat, Munifah; Jernita, Tanti (Dentika: Dental Journal, 2018)
Elderly is a natural process where changes in body tissue function include changes in oral tissues such as dry mouth, pale mucosa, mucosal thinning, attrition, and tooth loss. Maintaining the health of the oral cavity is one way to maintain body condition for the elderly. This study aims to determine the knowledge and behavior of oral health and oral health status in the elderly and its implications for general health. This study is an analytical study with a cross sectional approach, taking research subjects by purposive sampling and obtained 40 elderly people. The results showed that the average oral health status with poor criteria (DMF-T = 11,725; OHIS> 3.1 = 57.5%) and the elderly complained of impaired speech function, chewing and swallowing food. There is a significant relationship between knowledge and oral health behavior with DMFT (p = 0.85) and OHIS (p = 0.828). It was concluded that poor oral health status in the elderly could have implications for health problems both locally in the oral cavity and the body in general.Keywords: oral health status, elderly, health implications